2004
DOI: 10.1038/sj.bjc.6601824
|View full text |Cite
|
Sign up to set email alerts
|

The anticancer drug mithramycin A sensitises tumour cells to apoptosis induced by tumour necrosis factor (TNF)

Abstract: In this report we show that mithramycin considerably increases the direct cytotoxic effect of tumour necrosis factor (TNF) on tumour cells in vitro. Sensitisation to TNF-induced apoptosis was prevented by the broad caspase inhibitor zVAD-fmk, whereas overexpression of Bcl-2 had no effect. Mithramycin also potentiated cell death induced by Fas agonistic antibodies. In contrast, mithramycin reduced the percentage of cells undergoing apoptosis due to factor withdrawal. TNF-induced activation of NF-kappaB (NF-kB)-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 29 publications
2
19
0
Order By: Relevance
“…Thus we analyzed the induction of apoptosis in KG1a cells pre-treated with low doses of MMA by three anticancer drugs at clinical relevant doses (40 µM Aracytin, 5 µM Mitoxantrone and 10 µM Etoposide (VP16)) or FasL. At first, in agreement with Duverger's data, 20 we observed that MMA pretreatment sensitized KG1a cells to FasL-induced apoptosis (data not shown). As shown in Figure 6 and in agreement with previous reports, 29-31 chemotherapeutic drugs induced no apoptosis phenomenon in KG1a cells.…”
Section: Mma Regulates Different Protein Expression Levelsupporting
confidence: 85%
See 1 more Smart Citation
“…Thus we analyzed the induction of apoptosis in KG1a cells pre-treated with low doses of MMA by three anticancer drugs at clinical relevant doses (40 µM Aracytin, 5 µM Mitoxantrone and 10 µM Etoposide (VP16)) or FasL. At first, in agreement with Duverger's data, 20 we observed that MMA pretreatment sensitized KG1a cells to FasL-induced apoptosis (data not shown). As shown in Figure 6 and in agreement with previous reports, 29-31 chemotherapeutic drugs induced no apoptosis phenomenon in KG1a cells.…”
Section: Mma Regulates Different Protein Expression Levelsupporting
confidence: 85%
“…Nevertheless the effect of MMA alone on tumor cells is not well understood, but it has recently been shown that MMA can sensitize tumor cells to apoptosis induced by TNFα and anti-Fas antibody. 20 Therefore we postulated that MMA could activate Fas death pathway and/or sensitize resistant cells to druginduced apoptosis. Indeed, our study shows that high doses of MMA activate Fas apoptotic signaling pathway in FasL-sensitive Jurkat cells as well as in FasL-insensitive KG1a cells independently of FasL/Fas interaction.…”
Section: Introductionmentioning
confidence: 99%
“…Also mithramycin considerably increases the direct cytotoxic effect of TNF on tumor cells by acting on the balance of apoptotic factors [195]. In vitro, TNF-induced activation of NFkB-dependent gene expression is not modulated by mithramycin treatment, while FLIP protein levels are downregulated, indicating that mithramycin enhances TNF-induced PCD in an NFkB-independent manner by releasing the apoptotic brake FLIP.…”
Section: Other Tnf Sensitizersmentioning
confidence: 95%
“…Its mechanism of action has been proposed to interact with GC-rich domains of DNA contained in genes promoters (9), leading to gene transcription modulation, such as multidrug resistance gene (10), c-myc, or h-ras (11). It has recently been shown that mithramycin A can sensitize tumor cells to apoptosis induced by tumor necrosis factor-a and anti-Fas antibody (12,13). However, the underlying mechanisms of mithramycin A -induced sensitization are not well understood.…”
Section: Introductionmentioning
confidence: 99%